Antecedent Cities and Inter-referencing Effects: Learning from and Extending Beyond Critiques of Neoliberalisation. (August 2015) - Bunnell, Tim
Cities around the world are likened to, and remade with reference to, imaginings of antecedent urban experiences elsewhere. The paper begins by identifying inter-referencing effects associated with three different imaginings of urban antecedence in and beyond academic urban studies: the prototypical, paradigmatic city; the city which charts pathways to world city-ness; and the model or 'best' city. It is the effects of the third of these imaginings that has received the most sustained critical examination to date. The currently burgeoning literature on urban policy mobilities has proceeded methodologically by following actually existing intercity referential effects. The key argument in this paper is that critical policy mobilities research is problematic in largely reducing inter-referencing effects to neoliberalisation from above, but potentially very helpful for efforts to move beyond the EuroAmerican-centredness that has prevailed in imaginings of urban antecedence in Anglophone urban theory more widely.